1993
DOI: 10.1037/0022-006x.61.1.165
|View full text |Cite
|
Sign up to set email alerts
|

Influence of psychoactive substance use on the reliability of psychiatric diagnosis.

Abstract: The interrater reliability of diagnoses made on the basis of a structured interview for psychiatric patients with and without psychoactive substance use disorders (PSUDs) was examined. Forty-seven pairs of ratings by 9 different clinical interviewers were used. Results supported 3 major findings: (a) The interrater reliability for non-PSUD psychiatric diagnoses is quite high when a subject has no diagnosable PSUD; it is lower, though still substantial, when a PSUD is present. (b) Interviewers are not aware of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Several methodological problems have hampered research in this field, among them reduced reliability of the diagnosis of schizophrenia in the presence of concurrent substance abuse (Bryant et al 1992; Corty et al 1993); lack of specification of diagnostic criteria (Richard et al 1985; Rockwell and Ostwald 1988); nonuse of structured clinical interviews (Alterman et al 1981; O’Farrell et al 1983; Drake et al 1989 a ; Pristach and Smith 1990; Seibyl et al 1993; Shaner et al 1993); and uncertainty as to the relative contributions of schizophrenia and substance use to impaired functioning (Skinner and Sheu 1982). Also, severe problems associated with substance use may still be found even when DSM–IV criteria (American Psychiatric Association 1994) for substance abuse or dependence are not met (Helzer et al 1978; Dixon et al 1993), prevalence rates based on self-report questionnaires are consistently higher than those based on interviews (Turner et al 1992), and there appears to be a differential willingness to report past use over current use (McNagny and Parker 1992).…”
Section: Substance Abuse and The Course Of Schizophreniamentioning
confidence: 99%
“…Several methodological problems have hampered research in this field, among them reduced reliability of the diagnosis of schizophrenia in the presence of concurrent substance abuse (Bryant et al 1992; Corty et al 1993); lack of specification of diagnostic criteria (Richard et al 1985; Rockwell and Ostwald 1988); nonuse of structured clinical interviews (Alterman et al 1981; O’Farrell et al 1983; Drake et al 1989 a ; Pristach and Smith 1990; Seibyl et al 1993; Shaner et al 1993); and uncertainty as to the relative contributions of schizophrenia and substance use to impaired functioning (Skinner and Sheu 1982). Also, severe problems associated with substance use may still be found even when DSM–IV criteria (American Psychiatric Association 1994) for substance abuse or dependence are not met (Helzer et al 1978; Dixon et al 1993), prevalence rates based on self-report questionnaires are consistently higher than those based on interviews (Turner et al 1992), and there appears to be a differential willingness to report past use over current use (McNagny and Parker 1992).…”
Section: Substance Abuse and The Course Of Schizophreniamentioning
confidence: 99%
“…This differentiation generally can be made only after a period of abstinence. It has been shown that the presence of a substance use disorder substantially detracts from the diagnostic reliabilty of other Axis I disorders (Corty, Lehman, & Myers, 1993).…”
Section: Heterogeneity Of the Populationmentioning
confidence: 99%